Efektivitas Bimbingan Kelompok dengan Teknik Diskusi untuk Meningkatkan Kepercayaan Diri Siswa - Suryani, Aprilia Dewi; Kurniawan, Drajat Edy (Indonesian Journal of Educational Counseling, 2023)
EFFECTIVENESS OF GROUP GUIDANCE USING DISCUSSION TECHNIQUES TO INCREASE THE CONFIDENCE STUDENTS AT SMP. This study aims to determine the effectiveness of group guidance with discussion techniques to increase the confidence of class VIII students at SMP Negeri 1 Purwosari for the academic year 2021/2022. This type of research is quantitative, using a pre-experimental design with the type of one group pretest-posttest design. The data collection method in this study used a questionnaire with a population of all eighth grade students at SMP Negeri 1 Purwosari. The sample in this study took 10 students from the population using purposive sampling technique, and the data analysis technique in this study used T-test analysis. The results showed that the provision of discussion technique group guidance services was effective in increasing students' self-confidence. Based on the results of the t-test analysis, the value of t = -20,954 with p value = 0.000 <0.05, which means Ha is accepted, meaning that there is a positive and significant effect of providing discussion technique group guidance services to increase the self-confidence of Class VIII students in SMP Negeri 1 Purwosari Academic Year 2021/2022. It is hoped that schools and guidance and counseling teachers can apply discussion technique group guidance services effectively so that they can increase students' self-confidence.